The superpowers' playground : Djibouti and geopolitics of the Indo-Pacific in the 21st century - Gurjar, Sankalp (Researcher in international relations) (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"This book analyses the evolving geopolitics in the Indo-Pacific region and explains how Djibouti fits in the global strategies of four major powers-the US, China, Japan, and France. It shows how Djibouti is emerging as a key nation in the geopolitics of the Indo-Pacific, explores the interconnections between Djibouti and Indian as well as Pacific Oceans, and through Djibouti examines broader trends in contemporary great power politics in the Indo-Pacific region, including the Belt and Road Initiative of China. Moving beyond contemporary works on the region, the author integrates Africa and the Middle East with discussions on the Indo-Pacific to illustrate the coalescing of strategic geography from Eastern Africa to the Western coast of the Americas. A major intervention, the volume will be essential reading for scholars, practitioners and researchers of politics and international relations, security studies, African studies, peace and conflict studies, and maritime studies"--
Why Djibouti matters? -- A French homecoming? -- From Kilimanjaro to California -- The confluence of the two seas -- Building a New Silk Road.
Keywords: Geopolitics -- Indo-Pacific Region; Great powers; World politics -- 21st century; Djibouti -- Foreign relations; Djibouti -- Strategic aspects; POLITICAL SCIENCE / International Relations / General; POLITICAL SCIENCE / International Relations / Diplomacy; POLITICAL SCIENCE / Political Freedom & Security / International Security